PREVALENCE OF INTESTINAL PARASITIC INFECTIONS AMONG INTERNALLY DISPLACED PERSON’S AND HOST COMMUNITIES IN MUBI NORTH LOCAL GOVERNMENT AREA, ADAMAWA STATE, NIGERIA - Pukuma, M. S.; Augustine, M. L.; Enoch, N. (FUDMA JOURNAL OF SCIENCES, 2023)
A study on the Prevalence of Intestinal Parasitic Infections was carried out among Internally Displaced Persons and the host community in Mubi North Local Government Area of Adamawa State. 400 stool samples were collected from three communities namely, Barama,Yelwa and Wuro Hande. The Stool samples was processed using formol ether concentration technique and examined under microscope for the cyst of parasites with the aid of identification manual..121 were infected with a Prevalence rate of (30.3%). Eight Parasites species were encountered namely, Ascaris lumbricoides(36.1%), Schistosoma mansoni (22.5%), Ancylostoma duodenale (12.6%), Entamoeba histolytica (5.3%), Hymenolepis nana (2.6%), Enterobius vermicularis (3.0%), Entamoeba coli (6.0%) and Giardia lamblia (7.0%.). Ascaris lumbricoides was the most prevalent parasite while Hymenolepis nana was the least encountered. Internally Displaced Persons were more infected (34.5%) compared to the host community (26.0%), though statistically not significant P>0.05. Males were more infected among the IDPs (41.1%) than females 29.1%, while females (27.2%) were more infected than males (24.4%) in the host communities.. The study showed that infection was wide spread within the communities irrespective of settlement status. This could be attributed to poor personal hygiene, and indiscriminate dumping of waste, coupled with the challenges of portable water supply. There is the need for improvement in the availability of portable water supply and proper waste management in mubi and environs.